Governing cities : Asia's urban transformation - Hartley, Kris; Koh, Tommy (fwd.) (New York Routledge, 2020)
"This book presents the latest research on three issues of crucial importance to Asian cities: governance, liveability, and sustainability. Together, these issues canvass the salient trends defining Asian urbanization and are explored through an eclectic compendium of studies that represent the many voices of this diverse region. Examining the processes and implications of Asian urbanization, the book interweaves practical cases with theories and empirical rigour while lending insight and complexity into the towering challenges of urban governance. The book targets a broad audience including thinkers, practitioners, and students"--
Includes bibliographical references and index.
Keywords: Urbanization; City planning; Urban policy